Evolution of the Cell Wall Gene Families of Grasses - Penning, Bryan W.; McCann, Maureen C.; Carpita, Nicholas C. (Frontiers in Plant Science, 2019)
Grasses and related commelinid monocot species synthesize cell walls distinct in composition from other angiosperm species. With few exceptions, the genomes of all angiosperms contain the genes that encode the enzymes of substrate generation for their polysaccharide, phenylpropanoid and protein constituents. RNAseq analysis of transcripts expressed during development of the upper and lower internodes of maize (Zea mays) stem captured the expression of cell wall-related genes associated with primary or secondary wall formation. High levels of transcript abundances were not confined to genes associated with the distinct walls of grasses, but also of those associated with xyloglucan and pectin synthesis. Combined with proteomics data to confirm that expressed genes are translated, we propose that the distinctive cell wall composition of grasses results from sorting downstream from their sites of synthesis in the Golgi apparatus and hydrolysis of the uncharacteristic polysaccharides, and not from differential expression of synthases of grass-specific polysaccharides.